2008
DOI: 10.1175/2008jtecho549.1
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Calibration of Optode-Based Oxygen Sensors

Abstract: Eleven optode-based oxygen sensors were used for shipboard hydrographic casts in the North Pacific. Oxygen data from the optode sensors were compared with high-quality oxygen data obtained with discrete water samples, and the performance of the sensors was evaluated. The response of the sensing foil of the optode decreases with increasing ambient pressure, and this pressure effect was found to decrease the response by 3.2% (1000 dbar) Ϫ1 . A new calibration equation for the optode sensors was proposed. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
116
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(120 citation statements)
references
References 8 publications
(14 reference statements)
2
116
2
Order By: Relevance
“…For example, if Θ = 1, T = 5°C and pO 2 (P=0) = 200 mbar, then ƒO 2 (P=1000) = 229 mbar, representing an increase of approximately 14% per 1000 dbar. This dependence is much larger, and of opposite sign, to that observed by Uchida et al (2008), who found that the optode readings decreased by 3.2% per 1000 dbar.…”
Section: Pressure Compensationcontrasting
confidence: 68%
See 1 more Smart Citation
“…For example, if Θ = 1, T = 5°C and pO 2 (P=0) = 200 mbar, then ƒO 2 (P=1000) = 229 mbar, representing an increase of approximately 14% per 1000 dbar. This dependence is much larger, and of opposite sign, to that observed by Uchida et al (2008), who found that the optode readings decreased by 3.2% per 1000 dbar.…”
Section: Pressure Compensationcontrasting
confidence: 68%
“…To estimate the scale factor Θ, we use the Uchida et al (2008) finding that the optode response decreases by 3.2% per 1000 dbar and calibrate to a deep ocean temperature, T d [°C], and hydrostatic pressure, P d [dbar]. Multiplying the righthand side of Eq.…”
Section: Pressure Compensationmentioning
confidence: 99%
“…Finally, the adjustment recommended by Uchida et al [2] fits perfectly the behaviour of the sensor. The residuals don't exceed 3µmol/l which is in agreement with the manufacturer specifications and the scientific expectations.…”
Section: Calibration Of a 4330 Aanderaa Optodementioning
confidence: 75%
“…The pressure has already been identified by Uchida et al [2]. But calibrating optodes under pressure is a tricky procedure and is not yet in the habits.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation